2002
DOI: 10.1093/jat/26.4.222
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Cardenolides by Sonic Spray Ionization Liquid Chromatography-Ion Trap Mass Spectrometry—A Fatal case of Oleander Poisoning*

Abstract: Simultaneous determination of oleandrin and its three related compounds, desacetyloleandrin, oleandrigenin, and gitoxigenin in blood by using liquid chromatography-three-dimensional quadrupole mass spectrometry (LC-3DQMS) system equipped with sonic spray ionization (SSI) interface was conducted. This analyzing method was suitable for all of these compounds except gitoxigenin. The limits of detection of oleandrigenin and desacetyloleandrin from blood were 2 ng/mL and that of oleandrin was 3 ng/mL. The calibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 10 publications
2
17
0
1
Order By: Relevance
“…In contrast, the study of Wang et al [16] reported an oleandrin plasma concentration of 7 ng/ml for a volunteer 3 h after an intramuscular dose of 15 mg oleander extract for cancer treatment. This value is remarkably high compared to this case as well as other case reports [15,17], and can be explained only by an acquired tolerance of the volunteer.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…In contrast, the study of Wang et al [16] reported an oleandrin plasma concentration of 7 ng/ml for a volunteer 3 h after an intramuscular dose of 15 mg oleander extract for cancer treatment. This value is remarkably high compared to this case as well as other case reports [15,17], and can be explained only by an acquired tolerance of the volunteer.…”
Section: Resultssupporting
confidence: 57%
“…For example, in two cases of oleander poisoning in adults, comparable digoxin levels of 1.2 [8] and 1.5 ng/ml [9], respectively, in the blood samples were obtained; in these cases the immunoassays used yielded completely different results-mild cardiac symptoms [8] and death [9]. In contrast, well-defined toxicological data were published by Tracqui et al [15], who reported 1.1 ng/ml oleandrin (venous blood) in a non-fatal case that resulted in mild cardiac symptomatology, and by Arao et al [17], who reported 9.8 ng/ml oleandrin (heart blood) in a fatal poisoning.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…other proposed improvements in the ionization technique were the sonic spray devices and the introduction of APPI [20,[61][62][63][64][65]. The latter interface showed its usefulness in the analysis of rather nonpolar steroidal molecules.…”
Section: Purity Analysis and Impurity Profilingmentioning
confidence: 99%
“…Recently, very sensitive and specific LC-MS/MS methods for the identification and quantification of digoxin and some related cardiac glycosides like oleandrin in biological matrices have been described [5][6][7][8]13]. Compared to immunoassay methods, LC-MS/MS methods are valuable for the confirmation of oleander intoxication in human and animal clinical cases in which immunoassays for digoxin or digitoxin are used as screening tools, especially if such cases involve forensic investigations.…”
Section: Introductionmentioning
confidence: 99%